Design of Multi-Layer Optical Fibers with Ring Refractive Index to Reduce Dispersion and Increase Bandwidth in Broadband Optical Networks - Seifouri, M.; Karkhanehchi, M. M.; Rohani, S. (Engineering, Technology & Applied Science Research, 2012)
The main goal in this paper is to design single-mode optical fibers for DWDM networks, which are used today in rapid communications. These networks require low dispersion in a wide range of wavelengths. So, in this paper, multi-layer optical fibers with low dispersion value and flat dispersion slope in wavelength range of 1.5-1.6µm) are designed, using optimization algorithms.